7(x-4)-3=46

Simple and best practice solution for 7(x-4)-3=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-4)-3=46 equation:


Simplifying
7(x + -4) + -3 = 46

Reorder the terms:
7(-4 + x) + -3 = 46
(-4 * 7 + x * 7) + -3 = 46
(-28 + 7x) + -3 = 46

Reorder the terms:
-28 + -3 + 7x = 46

Combine like terms: -28 + -3 = -31
-31 + 7x = 46

Solving
-31 + 7x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '31' to each side of the equation.
-31 + 31 + 7x = 46 + 31

Combine like terms: -31 + 31 = 0
0 + 7x = 46 + 31
7x = 46 + 31

Combine like terms: 46 + 31 = 77
7x = 77

Divide each side by '7'.
x = 11

Simplifying
x = 11

See similar equations:

| 2/5(25z-30)=3/5(12z+16) | | 12-8x=137-43x | | 81xy^3+3x^4=0 | | 122-3x=15x+20 | | 4(2x-8)-2=4(x-4)+6 | | 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 | | 4xy^4-32xy=0 | | -9(x-4)-3=46 | | 0.5x-0.1(5-x)=2.2 | | 77/121 | | -7-6=7-8x | | -3(2x+1)=21 | | 5(4x-3)=11 | | 4y^3+12y^2+5y=0 | | 23=49-7x | | f(x)=x^3-2x^2+2x-6 | | 20-9w=4(15-1w) | | 11+9lnx=6 | | y+11=19 | | 9p+-5=1 | | 5x=81.2 | | 2x^2=-5x-10 | | z^(-3)/z^(-7) | | 87=2x-3(5x-3) | | -4(-2+2x)=-32 | | (9m-15)6=18 | | x^2-2x-15/6x^2-54 | | 5x^2+7x=4 | | -4(-4-6x)=88 | | 3x-8=58-2x |

Equations solver categories